The effect of lengths of branched-chain fatty alcohols on the efficacy and safety of docetaxel-prodrug nanoassemblies - Shuo Wang; Tian Liu; Yuetong Huang; Chaoying Du; Danping Wang; Xiyan Wang; Qingzhi Lv; Zhonggui He; Yinglei Zhai; Bingjun Sun; Jin Sun (Elsevier, 2024)
The self-assembly prodrugs are usually consisted of drug modules, activation modules, and assembly modules. Keeping the balance between efficacy and safety by selecting suitable modules remains a challenge for developing prodrug nanoassemblies. This study designed four docetaxel (DTX) prodrugs using disulfide bonds as activation modules and different lengths of branched-chain fatty alcohols as assembly modules (C16, C18, C20, and C24). The lengths of the assembly modules determined the self-assembly ability of prodrugs and affected the activation modules' sensitivity. The extension of the carbon chains improved the prodrugs' self-assembly ability and pharmacokinetic behavior while reducing the cytotoxicity and increased cumulative toxicity. The use of C20 can balance efficacy and safety. These results provide a great reference for the rational design of prodrug nanoassemblies.